Comparison of different rules to deal with incomplete information: perspectives of mediation - Sarabando, Paula (2015)
In bilateral Negotiation Analysis, the literature often considers the case with complete information. In this context, since the value (or utility) functions of both parties are known, it is not difficult to calculate the Pareto frontier (or efficient frontier) and the Pareto efficient solutions for the negotiation. Thus rational actors can reach agreement on this frontier. However, these approaches are not applied in practice when the parties do not have complete information. Considering that the additive value (or utility) function is used, often it is not easy to obtain precise values for the scaling weights or the levels’ value in each issue. We compare four decision rules that require weaker information, namely ordinal information on weights and levels, to help a mediator suggesting an alternative under these circumstances. These rules are tested using Monte-Carlo simulation, considering that the mediator would be using one of three criteria: maximizing the sum of the values, maximizing the product of the excesses regarding the reservation levels, or maximizing the minimal proportion of potential. Simulations asses how good is the alternative chosen by each rule, computing the value loss with respect to the alternative that would be suggested if there was precise cardinal information and determining if the chosen alternative is efficient or, if not, how far is the nearest efficient alternative. We also provide guidelines about how to use these rules in a context of selecting a subset of the most promising alternatives, considering the contradictory objectives of keeping a low number of alternatives yet not excluding the best one. A further issue we investigate is whether using only ordinal information leads to treat one of the parties unfairly, when compared to a situation in which precise cardinal values were used instead.